CHIKUNGUNYA DRUG TARGET DATABASE: A COMPREHENSIVE DATABASE OF CHIKUNGUNYA DRUG TARGETS - KORI, PRIYANKA; B Madagi, Shivakumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Chikungunya is a viral infection transmitted by the Aedes mosquito to humans. Currently, there is no approved treatment for the infection. Clinical trials have been carried out to identify candidate drug molecules. There is no existing repository for determining the information pertaining to drug targets of chikungunya. The current study aims to develop a comprehensive database of chikungunya drug targets. Methods: Literature review is carried out to determine the available drug targets for chikungunya with the help of several open source biological repositories. The database consists of 23 viral strains, 19 drugs targets, and 7 drugs. Further manual annotation is performed to identify the relevant drug targets. For each of these drug targets identified, an illustrative pathway is constructed depicting the role of drug targets in the viral infection. Results: The chikungunya drug target database (CDTD) was constructed based on the three-tier architecture in XAMPP (Windows Apache MySQL Perl PHP) platform. The database comprised 23 viral isolates, 19 drug targets, and 7 currently used drugs specific to chikungunya infection. For each of the drug targets, a mechanistic pathway is designed to illustrate the role of drug targets and the mechanical pathway in chikungunya infection. Conclusion: CDTD is a specialized database which is designed to provide comprehensive information pertaining to viral drug targets. The database can be utilized from researchers interested in the virology of chikungunya further providing drug target information. Availability: The database is freely available at http://www.biocdtd.org/. Keywords: Chikungunya virus, Drug targets, Viral isolates, Drugs, Pathways.